Contribuições de letras de canções para o trabalho com o léxico no ensino fundamental: algumas possibilidades - Herwig, Eladio Camargo (2021)
The school has a fundamental role in the intellectual development of students, and lexical expansion is important during anyone's life. Knowing how to describe the meanings of the lexicon and reveal its mysteries will contribute to a better understanding of the word, the text, the speech. Thus, it is from this perspective that this work offers the Portuguese language teacher theoretical and practical subsidies with the preparation of this dissertation and an Activities Notebook, which contains activities with the lexicon of song lyrics to be worked on in the classroom. The Notebook presents a didactic proposal based on the didactic sequence of Dolz, Noverraz and Schneuwly (2004). This didactic proposal used the song lyrics genre as a guide for the classes and contributed to the lexical and cultural enrichment of students, through activities based on the assumptions of Lexicology and Lexicography. The theoretical basis was based on authors such as: Dias (2004), (2009); Antunes (2012), (2003), (2009), (2010); Krieger (2012); Pottier (1968), Polguère (2018) among others. Although the proposal was applied remotely, due to social isolation due to the Corona virus pandemic, the methodology, inspired by Thiollent's action research, proved to be unprecedented in this format and important for carrying out the intervention. The Activity Notebook is attached to the end of this dissertation. Finally, in this work, we defend the use of song lyrics as a strategy for teaching the mother tongue, and we want to show that its use in the classroom can awaken students' interest in reading and text production, increase vocabulary repertoire, increase knowledge of the world, discuss relevant topics to living in society, etc.